A cone on Mercury: Analysis of a residual central peak encircled by an explosive volcanic vent. (April 2015) - Thomas, Rebecca J.; Lucchetti, Alice; Cremonese, Gabriele; Rothery, David A.; Massironi, Matteo; Re, Cristina; Conway, Susan J.; Anand, Mahesh
Abstract: We analyse a seemingly-unique landform on Mercury: a conical structure, encircled by a trough, and surrounded by a 23, 000 km 2 relatively bright and red anomaly of a type interpreted elsewhere on the planet as a pyroclastic deposit. At first glance, this could be interpreted as a volcanically-constructed cone, but if so, it would be the only example of such a landform on Mercury. We make and test the alternative hypothesis that the cone is the intrinsic central peak of an impact crater, the rim crest of which is visible beyond the cone-encircling trough, and that the trough is a vent formed through explosive volcanism that also produced the surrounding bright, red spectral anomaly. We test this hypothesis by comparing the morphology of the cone and the associated landform assemblage with morphologically-fresh impact craters of the same diameter as the putative host crater, and additionally, by modelling the original morphology of such a crater using a hydrocode model. We show that the present topography can be explained by formation of a vent completely encircling the crater's central peak and also make the observation that explosive volcanic vents frequently occur circumferential to the central peaks of impact craters on Mercury. This indicates that, although this cone initially appears unique, it is in fact an unusually well-developed example of a common process by which impact-related faults localize magma ascent near the centre of impact craters on Mercury, and represents an extreme end-member of the resulting landforms. Highlights: Identification of steep-sided cone with a volcanic association. Morphological analysis indicates it is the residual peak of an impact crater. Evidence for localization of explosive volcanism through crater-related fractures.